2014
DOI: 10.1097/wno.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Disease

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a multifocal inflammatory disorder that causes tumefactive lesions with a dense lymphoplasmacytic infiltrate rich in IgG4 plasma cells and storiform-pattern fibrosis. The clinical symptoms are relatively mild, and the condition is usually recognized by organ swelling and damage. When referring to the ophthalmic manifestations of IgG4-RD, the term IgG4-related ophthalmic disease (IgG4-ROD) is used. IgG4-ROD is characterized by bilateral lacrimal gland enlargement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…Previous data have suggested that IgG4-RD has a particular tropism for cranial nerves [2426]. In addition, it has been reported that IONE can oppress the optic nerve at the orbital apex [27]. However, in this study, we observed no IONE oppression related cases, while most oppressions were caused by pseudo tumor.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous data have suggested that IgG4-RD has a particular tropism for cranial nerves [2426]. In addition, it has been reported that IONE can oppress the optic nerve at the orbital apex [27]. However, in this study, we observed no IONE oppression related cases, while most oppressions were caused by pseudo tumor.…”
Section: Discussioncontrasting
confidence: 70%
“…[ 28 ] On the contrary, optic nerve involvement is uncommon in IgG4-RD. [ 29 34 ] It is most often unilateral [ 35 ] and due to compression of the optic nerve by enlarged orbital structures affected by IgG4-ROD; [ 36 38 ] in a series of patients with IgG4-ROD, compressive optic neuropathy was found on orbital imaging in 9.2% of the cases. [ 35 ] In some cases a meningeal infiltration of the optic nerve is found on imaging, suggesting perineuritis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] In view of this only case, it seems that IgG4-related optic neuropathy may rarely be due to direct infiltration of the optic nerve by IgG4-related inflammation (by analogy with what is found in the biopsies of the branches of the trigeminal nerve, but this hypothesis is subject to confirmation by an actual optic nerve biopsy). [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…Orbital involvement in IgG4-RD has been previously reported to affect nearly every orbital structure, including lacrimal glands, extra-ocular muscles and the trigeminal nerve ( 16 , 17 ). The term IgG4-related ophthalmic disease (IgG4-ROD) has been suggested for IgG4-RD with ophthalmic involvement ( 18 ). According to Kashii ( 18 ), IgG4-ROD is characterized by bilateral lacrimal gland enlargement accompanied by three distinctive features, including infraorbital nerve enlargement, extraocular myositis and compressive optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The term IgG4-related ophthalmic disease (IgG4-ROD) has been suggested for IgG4-RD with ophthalmic involvement ( 18 ). According to Kashii ( 18 ), IgG4-ROD is characterized by bilateral lacrimal gland enlargement accompanied by three distinctive features, including infraorbital nerve enlargement, extraocular myositis and compressive optic neuropathy. Comparing the characteristics of the patient of the current study to this classification, we note that an upper eyelid mass was present, which was consistent with lacrimal gland enlargement; however, this disappeared spontaneously and prior to methylprednisolone treatment.…”
Section: Discussionmentioning
confidence: 99%